13 - Ethical and Methodological Issues in HIV/Aids Social Science Research - Zachary Arochi Kwena (CODESRIA Bulletin, 2003)
As a mainly sexually transmitted infection, HIV/Aids basically takes advantage of how we live our sexuality. Since biomedical research has so far not been able to provide a cure or vaccine, the only option we are left with is to change the behaviours that enable HIV/Aids to spread. To do so, however, we first need reliable data on the behavioural aspects of the HIV/Aids pandemic. Unfortunately this has proved challenging in Africa due to the fact that sex, in many African communities, is a hidden issue and is considered taboo to discuss openly. The question then is: how can we successfully – and ethically – collect this data despite the reluctance of people to discuss sex-related issues honestly and openly? This paper explores the ethical and methodological considerations of conducting research on the sexual aspects of HIV/Aids in the African context.